The fungus Acremonium alternatum enhances salt stress tolerance by regulating host redox homeostasis and phytohormone signaling - Berková, Veronika; Berka, Miroslav; Štěpánková, Lenka; Kováč, Ján; Auer, Susann; Menšíková, Simona; Ďurkovič, Jaroslav; Kopřiva, Stanislav; Ludwig-Müller, Jutta; Brzobohatý, Břetislav; Černý, Martin (Physiologia plantarum, 2024)
While endophytic fungi offer promising avenues for bolstering plant resilience against abiotic stressors, the molecular mechanisms behind this biofortification remain largely unknown. This study employed a multifaceted approach, combining plant physiology, proteomic, metabolomic, and targeted hormonal analyses to illuminate the early response of Brassica napus to Acremonium alternatum during the nascent stages of their interaction. Notably, under optimal growth conditions, the initial reaction to fungus was relatively subtle, with no visible alterations in plant phenotype and only minor impacts on the proteome and metabolome. Interestingly, the identified proteins associated with the Acremonium response included TUDOR 1, Annexin D4, and a plastidic K+ efflux antiporter, hinting at potential processes that could counter abiotic stressors, particularly salt stress. Subsequent experiments validated this hypothesis, showcasing significantly enhanced growth in Acremonium-inoculated plants under salt stress. Molecular analyses revealed a profound impact on the plant's proteome, with over 50% of salt stress response proteins remaining unaffected in inoculated plants. Acremonium modulated ribosomal proteins, increased abundance of photosynthetic proteins, enhanced ROS metabolism, accumulation of V-ATPase, altered abundances of various metabolic enzymes, and possibly promoted abscisic acid signaling. Subsequent analyses validated the accumulation of this hormone and its enhanced signaling. Collectively, these findings indicate that Acremonium promotes salt tolerance by orchestrating abscisic acid signaling, priming the plant's antioxidant system, as evidenced by the accumulation of ROS-scavenging metabolites and alterations in ROS metabolism, leading to lowered ROS levels and enhanced photosynthesis. Additionally, it modulates ion sequestration through V-ATPase accumulation, potentially contributing to the observed decrease in chloride content.
Keywords: signální transdukce; Abscisic Acid; Salt Tolerance; kyselina abscisová; Signal Transduction; regulátory růstu rostlin; Oxidation-Reduction; Salt Stress; fotosyntéza; rostlinné proteiny; Photosynthesis; homeostáza; Plant Proteins; Brassica napus; oxidace-redukce; Plant Growth Regulators; Homeostasis; Acremonium; tolerance k soli; solný stres